INDIRECT EFFECTS OF 10-VALENT PNEUMOCOCCAL CONJUGATE VACCINE AGAINST ADULT PNEUMOCOCCAL PNEUMONIA IN RURAL WESTERN KENYA - Bigogo, Godfrey M. (Clin Infect Dis, 2019)
BACKGROUND: Data on pneumococcal conjugate vaccine (PCV) indirect effects in low-income countries with high HIV burden are limited. We examined adult pneumococcal pneumonia incidence before and after 10-valent PCV introduction in Kenya in 2011. METHODS: From 1/1/2008 to 12/31/2016, we conducted surveillance for acute respiratory infection (ARI) among ~12,000 adults (≥18 years) in western Kenya, where HIV prevalence ~17%. ARI cases (cough or difficulty breathing or chest pain, plus temperature ≥38.0(◦)C or oxygen saturation <90%) presenting to a clinic underwent blood culture and pneumococcal urine antigen testing (UAT). We calculated ARI incidence and adjusted for healthcare seeking using data from household visits. The proportion of ARI cases with pneumococcus detected among those with complete testing (blood culture and UAT) was multiplied by adjusted ARI incidence to estimate pneumococcal pneumonia incidence. RESULTS: Pre-PCV (2008–2010), crude and adjusted ARI incidence were 3.14 and 5.30/100 person-years-observation (pyo), respectively. Among ARI cases, 39.0% (340/872) had both blood culture and UAT; 21.2% (72/340) had pneumococcus detected, yielding baseline pneumococcal pneumonia incidence of 1.12/100 pyo (95% confidence interval [CI] 1.0–1.3). In each post-PCV year (2012–2016), pneumococcal pneumonia incidence was significantly lower than baseline; with incidence rate ratios (IRR) of 0.53 (95%CI 0.31–0.61) in 2012 and 0.13 (95%CI 0.09–0.17) in 2016. Similar declines were observed in HIV-infected (IRR 0.13, 95%CI 0.08–0.22), and HIV-uninfected (IRR 0.10, 95%CI 0.05–0.20). CONCLUSIONS: Adult pneumococcal pneumonia declined in western Kenya following 10-valent PCV introduction, likely reflecting vaccine indirect effects. Evidence of herd protection is critical for guiding PCV policy decisions in resource-constrained areas.